Guidelines for failure investigation - Barrow, Richard S.; Anthony, Ronald W. (Wood scientist); Beasley, Kimball J.; Verhulst, Stewart M. (American Society of Civil Engineers, 2018)
"This technical report outlines the fundamental steps that assist forensic engineers in tailoring their forensic investigations of failures and performance problems associated with structures and building systems"--